1983
DOI: 10.1177/001316448304300417
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Validity of the Armed Services Vocational Aptitude Battery (ASVAB), Forms 8, 9 and 10: 1981 Army Applicant Sample

Abstract: The purpose of this paper was to examine the factor structure of the Armed Services Vocational Aptitude Battery (ASVAB), Forms 8, 9, and 10. This standardized multiple cognitive abilities battery is the primary selection and classification instrument used by all military services. It consists of eight power and two speed tests. In this investigation the ASVAB 8/9/10 factor structure was compared with that observed for previous samples and for previous forms of the ASVAB. The similarity of factor structure for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 1 publication
4
31
0
Order By: Relevance
“…The three most important findings are: (1) the general factor (psychometric g) accounts for approximately 60 percent of the total variance (Kass, Mitchell, Grafton, & Wing, 1983;Welsh, Watson, & Ree, 1990), (2) four factors have been identified and replicated across studies (Kass et al, 1983;, and (3) the four factors have been replicated for males, females, Blacks, Whites, and Hispanic subgroups separately (Kass et al, 1983). The four factors and ASVAB subtests that have substantial loadings are:…”
Section: Asvab Compositesmentioning
confidence: 96%
See 1 more Smart Citation
“…The three most important findings are: (1) the general factor (psychometric g) accounts for approximately 60 percent of the total variance (Kass, Mitchell, Grafton, & Wing, 1983;Welsh, Watson, & Ree, 1990), (2) four factors have been identified and replicated across studies (Kass et al, 1983;, and (3) the four factors have been replicated for males, females, Blacks, Whites, and Hispanic subgroups separately (Kass et al, 1983). The four factors and ASVAB subtests that have substantial loadings are:…”
Section: Asvab Compositesmentioning
confidence: 96%
“…(1) Verbal (WK and PC) (2) Speed (CS and NO) (3) Quantitative (AR and MK) (4) Technical (AS, MC, and EL) GS has loaded on the Verbal factor (Ree, Mullins, Mathews, & Massey, 1982) and has yielded split-loadings on the Verbal and Technical factors (Kass et al, 1983). Otherwise this factor solution is relatively straight forward and is highly replicable.…”
Section: Asvab Compositesmentioning
confidence: 99%
“…Only minor differences exist between these and the four factor solutions reported by Kass et al (1982) and Ree et al (1981). These four factors can be interpreted as Verbal, Speed, Math, and Technical, as noted in the introduction.…”
Section: Resultsmentioning
confidence: 67%
“…Previous research (Kass, Mitchell, Grafton, & Wing, 1982;Ree, Mullins, Mathews, & Massey, 1981 ) on the factor structure of ASVAB has demonstrated that the constructs measured by ASVAB can be reasonably described by four factors. With minor variation, these are: Verbal (General Science, Word Knowledge, and Paragraph Comprehension), Speed (Coding Speed and Numerical Operations), Math (Arithmetic Reasoning and Mathematical Knowledge) and Technical (Auto/Shop Information, Mechanical Comprehension, and Electronics Information).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation